Compact Mass Flow Meter Based on a Micro Coriolis Flow Sensor - Remco Wiegerink; Theo Lammerink; Jarno Groenesteijn; Jeroen Haneveld; Ferry Postma; Marcel Katerberg; Wouter Sparreboom; Jan van de Geest; Joost Lötters (Micromachines, 2013)
In this paper we demonstrate a compact ready-to-use micro Coriolis mass flow meter. The full scale flow is 1 g/h (for water at a pressure drop < 1 bar). It has a zero stability of 2 mg/h and an accuracy of 0.5% reading for both liquids and gases. The temperature drift between 10 and 50 °C is below 1 mg/h/°C. The meter is robust, has standard fluidic connections and can be read out by means of a PC or laptop via USB. Its performance was tested for several common gases (hydrogen, helium, nitrogen, argon and air) and liquids (water and isopropanol). As in all Coriolis mass flow meters, the meter is also able to measure the actual density of the medium flowing through the tube. The sensitivity of the measured density is ~1 Hz.m3/kg.